Curcumin stably interacts with DNA hairpin through minor groove binding and demonstrates enhanced cytotoxicity in combination with FdU nucleotides - Ghosh, Supratim; Mallick, Sumana; Das, Upasana; Verma, Ajay; Pal, Uttam; Chatterjee, Sabyasachi; Nandy, Abhishek; Saha, Krishna D.; Maiti, Nakul Chandra; Baishya, Bikash; Suresh Kumar, G.; Gmeiner, William H. (Biochimica et biophysica acta, 2018)
We report, based on biophysical studies and molecular mechanical calculations that curcumin binds DNA hairpin in the minor groove adjacent to the loop region forming a stable complex. UV–Vis and fluorescence spectroscopy indicated interaction of curcumin with DNA hairpin. In this novel binding motif, two ɣ H of curcumin heptadiene chain are closely positioned to the A16-H8 and A17-H8, while G12-H8 is located in the close proximity of curcumin α H. Molecular dynamics (MD) simulations suggest, the complex is stabilized by noncovalent forces including; π-π stacking, H-bonding and hydrophobic interactions. Nuclear magnetic resonance (NMR) spectroscopy in combination with molecular dynamics simulations indicated curcumin is bound in the minor groove, while circular dichroism (CD) spectra suggested minute enhancement in base stacking and a little change in DNA helicity, without significant conformational change of DNA hairpin structure. The DNA:curcumin complex formed with FdU nucleotides rather than Thymidine, demonstrated enhanced cytotoxicity towards oral cancer cells relative to the only FdU substituted hairpin. Fluorescence co-localization demonstrated stability of the complex in biologically relevant conditions, including its cellular uptake. Acridine orange/EtBr staining further confirmed the enhanced cytotoxic effects of the complex, suggesting apoptosis as mode of cell death. Thus, curcumin can be noncovalently complexed to small DNA hairpin for cellular delivery and the complex showed increased cytotoxicity in combination with FdU nucleotides, demonstrating its potential for advanced cancer therapy. [Display omitted] •Binding motif of curcumin with short DNA hairpin was investigated.•High resolution spectroscopy in combination with molecular dynamics simulations was used for the study.•Curcumin binds in the minor groove of the DNA hairpin and shape complementarity played a significant role.•Curcumin binding enhanced the cytotoxicity of FdU containing DNA hairpin towards oral cancer cells.•FdU-hairpin:curcumin complex is stable at biological condition and suitable for intracellular uptake.